PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII4 SMP NEGERI 22 PEKANBARU - Sari, Putri Maya; Anggraini, Rini Dian; Heleni, Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research is low of mathematics learning outcomes of class VIII4 of 22 Junior High School Pekanbaru in second semester of the 2016/2017 academic year. Subject of this research are 38 students, consist of 19 male and 19 female student with heterogenous level of academic capabilities. The type of this research is the Classroom Action Research that has purpose to improve the learning proses and to increase student’s mathematic learning outcomes by applied the cooperative learning with Talking Stick Type. This research consists of two cycles that each cycle composed of 4 stages, such as planning, implementation, observation and reflection. At every end of a cycle, math achievement test will be held. The research instrument consists of learning devices that involve Syllabus, Lesson Plan and Worksheet, and instrument data collector that involve the observation sheet and math achievement test. Observation sheets is analyzed by narrative descriptive analysis and math achievement test analyzed by statistic descriptive analysis. The result of the research showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test II are respectively 18 person (47,36%), 23 person (60,52%) and 30 person (78,94%). Results of this research indicates that application of Cooperative Learning with Talking Stick Type can improve learning process and increase mathematics learning outcomes from the students of class VIII4 of 22 Junior High School Pekanbaru in second semester of the 2016/2017 academic year at Basic Competencies 5.3 Calculates the surface area and volume of the Beam, Cube, Prism and Pyramid.Key Words: Cooperative Learning, Talking Stick Type, Learning Process, Student Mathematics Learning Outcomes